Sophie Grigson: Eat Your Greens: Network Books & Sophie Grigson & William Black: Travels a la Carte - D., J.M. (Petits Propos Culinaires, 1994)
Sophie Grigson: Eat Your Greens: Network Books (BBC Books) London, 1993: ISBN 0 563 36738: 272 pp, colour photographs Jess Koppel, index, £15.99 (also available in p'back). Sophie Grigson & William Black: Travels a la Carte: same publisher, 1994: ISBN 0 563 37017 3: 224 pp, colour food photographs Jess Koppel, index, £15.99.